1993
DOI: 10.1002/iroh.19930780114
|View full text |Cite
|
Sign up to set email alerts
|

Organic Matter, Carbon, Nitrogen and Phosphorus Contents of the Mesozooplankton, Mainly Acartia clausi, in a Tropical Brackish Lagoon (Ebrié Lagoon, Ivory Coast)

Abstract: Mesozooplankton samples were collected over a period of one year in five stations of the Ebrié lagoon and analysed for organic, carbon, nitrogen and phosphorus contents. When zooplankton was dominated by A. clausi, body composition was relatively stable compared with the broad variability of environmental factors (mainly salinity, food abundance and composition), although a negative hypothetic influence of salinity may have occurred. Body composition was comparable when zooplankton was dominated by Pseudodiapt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…The individual carbon weights were calculated using length-dry weight relationships from Jerling & Wooldridge (1991) for P. hessei and from Bottrell et al (1976) for the other taxa. Dry weights were converted into carbon weights using an average carbon:dry weight ratio of 45% (Pagano & Saint-Jean, 1993). The mean zooplankton densities in the experimental jars were: 16 ind l -1 (150 lg C l -1 ) for P. hessei (adults), 80 ind l -1 (144 lg C l -1 ) for M. ogunnus (mixture of copepodites and adults), 100 ind l -1 (149 lg C l -1 ) for M. micrura (adult females), 300 ind l -1 (150 lg C l -1 ) Table 2 Experiments with Pseudodiaptomus hessei: concentration (Conc.)…”
Section: Methodsmentioning
confidence: 99%
“…The individual carbon weights were calculated using length-dry weight relationships from Jerling & Wooldridge (1991) for P. hessei and from Bottrell et al (1976) for the other taxa. Dry weights were converted into carbon weights using an average carbon:dry weight ratio of 45% (Pagano & Saint-Jean, 1993). The mean zooplankton densities in the experimental jars were: 16 ind l -1 (150 lg C l -1 ) for P. hessei (adults), 80 ind l -1 (144 lg C l -1 ) for M. ogunnus (mixture of copepodites and adults), 100 ind l -1 (149 lg C l -1 ) for M. micrura (adult females), 300 ind l -1 (150 lg C l -1 ) Table 2 Experiments with Pseudodiaptomus hessei: concentration (Conc.)…”
Section: Methodsmentioning
confidence: 99%
“…Molar bacterial and algal C:P ratios have been reported to vary between 15 and 170:1 and 80 and 900:1, respectively ( Tables 1 and 2). Crustacean zooplankton tend to be homeostatic in their carbon (C) to phosphorus (P) ratios (Anderson and Hessen, 1991; Sterner, 1993) and have low molar C:P ratios of about 100–130:1 (Hessen and Lyche, 1991; Pagano and St. Jean, 1993). Although recent findings showed that P‐limited daphnids can lose a significant amount of their P‐content (DeMott et al , 1998), zooplankton are much less variable in stoichiometry than algae and bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Specimens of a mixed set of at least 30 individuals from all 21 stations were measured. Individual DWs were converted into carbon (C) using a C/DW ratio of 0.045 (Pagano and Saint-Jean, 1993). …”
Section: Sampling and Data Analysismentioning
confidence: 99%